The Routledge history handbook of Central and Eastern Europe in the twentieth century.
1 online resource
Keywords: Challenges of Modernity offers a broad account of the social and economic history of Central and Eastern Europe in the twentieth century and asks critical questions about the structure and experience of modernity in different contexts and periods. This volume focuses on central questions such as: How did the various aspects of modernity manifest themselves in the region, and what were their limits? How was the multifaceted transition from a mainly agrarian to an industrial and post-industrial society experienced and perceived by historical subjects? Did Central and Eastern Europe in fact approximate its dream of modernity in the twentieth century despite all the reversals, detours and third-way visions? Structured chronologically and taking a comparative approach, a range of international contributors combine a focus on the overarching problems of the region with a discussion of individual countries and societies, offering the reader a comprehensive, nuanced survey of the social and economic history of this complex region in the recent past. The first in a four-volume set on Central and Eastern Europe in the twentieth century, it is the go-to resource for those interested in the challenges of modernity faced by this dynamic region.